ANALISA KEDISIPLINAN KERJA PEGAWAI DI MASA PANDEMI COVID- I9 ( STUDI PADA KANTOR DESA LABUAN BADAS SUMBAWA ) - Asmini Asmini; Ismawati Ismawati; Wahyu Haryadi; Subhan Purwadinata (Jurnal Ilmiah Hospitality, 2022)
The legal protection of the PP police unit in controlling street vendors (PKL), while the author chose this title because until now the PP Satpol policy is mainly related to controlling street vendors, it still feels lacking due to several factors. The main problem in the article is to discuss how the duties and roles of the Satpol PP (Pamong Praja Police) functions are, then followed by law enforcement of the Satpol PP in controlling street vendors (PKL). The conclusion from the discussion discussed is that the SatPol PP includes the role of law enforcement in the police unit in controlling street vendors. In carrying out the duties of the Satpol PP, among others, is carrying out environmental order by carrying out. Supervision by Satpol PP in Controlling Street Vendors. The supervision carried out by the Satpol PP officers is that the Satpol PP officers carry out patrols. The practice carried out by street vendors in using public facilities is very disturbing to other people, especially pedestrians. The sidewalk, a place that should be used by pedestrians to walk, is misused by street vendors to sell, so pedestrians walk on the highway and cause congestion. The practice disturbs a lot of people causing congestion and chaos on the Road. The methodology used in this research is normative research, which will use a descriptive type of research with a normative juridical approach, based on applicable laws and regulations.